Intervention Programs and Determinant Factors of Stunting Prevalence in Indonesia: An Ecological Study - Charoline Adelyn Dwi Della; Hadi Riyadi; Yayuk Farida Baliwati (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Stunting remains a critical public health challenge in Indonesia. According to recent national reports, the prevalence still exceeds the WHO threshold, indicating a persistent burden.  This study aimed to analyze the effectiveness of intervention programs and identify the determinants of stunting prevalence at the provincial level in Indonesia. This ecological study uses secondary data from 2022 covering 34 provinces, sourced from official ministry and agency reports. The study variables consisted of stunting prevalence; contributing factors (health, nutrition intake, socioeconomic); and intervention programs (nutrition, health, environment, social). Data were analyzed using Pearson and Spearman tests. The results showed a national stunting prevalence average of 23.29 ± 6.47%, with 50% of provinces classified in the high category. Factors positively correlated with stunting (p<0.05) included low birth weight, poverty, food expenditure, access to proper drinking water, and the family hopes program (PKH), all of which were associated with higher stunting prevalence. Conversely, factors negatively associated with stunting (p<0.05) included dietary pattern score, birth certificate ownership, average years of schooling, non-food expenditure, supplementary feeding for pregnant women with chronic energy deficiency (CED) and underweight toddlers, iron supplementation for pregnant women and adolescent girls, health professional-assisted delivery, antenatal care visits, immunization, postpartum family planning, and access to proper sanitation, all of which were linked to lower stunting prevalence. In conclusion, stunting is driven by multidimensional health, nutritional, and structural factors. Thus, integrated multisectoral interventions are  essential to accelerate stunting reduction.